Contribution for the Study of Inductive Fault Current Limiters in Electrical Distribution Grids - Arsénio, Pedro Miguel Lucas (2017)
Inductive type fault current limiters with superconducting tapes are emerging devices that provide technology for the advent of modern electrical grids, helping to mitigate operational problems that such grids can experience as well as preventing the often-costly upgrade of power equipment, namely protections. The development of such limiters leads to several design challenges regarding the constitutive parts of those devices, namely the magnetic core, primary winding and superconducting secondary. Fault current limiters are required to operate at overcurrents during a certain amount of time. The operation at such currents can lead to harmful effects due to mechanical, electromagnetic and thermal stresses, especially in the superconducting tape. Since the operation principle of fault current limiters envisaged in this thesis is based on the superconducting-normal transition of superconducting materials, the study of its transient behaviour is an important research subject. In this work, an electromagnetic methodology based on the characteristics of the constitutive parts of the limiters, previously developed and compared to finite element modelling simulations with very similar results, is simulated and validated with experimental results. Furthermore, the current in the superconducting tape is modelled from experimental results with the purpose of predicting the temperature of the material during normal and fault operation conditions, by employing a thermal-electrical analogy. These results are also compared to experimental measurements. A fast simulation tool, with computation times in the order of minutes, is also developed in Simulink, from Matlab environment. With the developed simulation tool, it is possible to quickly predict the transient electromagnetic-thermal behaviour of an inductive type fault current limiter operating in electrical grids, namely the line current and primary linked flux, as well as current and temperature in the superconducting tape.